ANALISA KELAYAKAN FINANSIAL PENERBANGAN RUTE BANDA ACEH – NAGAN RAYA - Tri Handayani; Renni Anggraini; Muhammad Isya (JURNAL TEKNIK SIPIL, 2017)
Abstract: Nagan Raya is located in the western part of Aceh Province. This regency is 287 km from Banda Aceh where the main mode of transportation is land transportation with travel time of approximately 6 hours. The land route to this regency through the mountains that during the rainy season often occurs landslides. So that air transport is needed that can help smooth mobility and improve the economy of the population and can anticipate the distribution of aid, evacuation of victims quickly when the disaster. PT Susi Pudjiastuti is a pioneering aviation operator serving Banda Aceh - Nagan Raya route. This study aims to determine the demand for passengers and financial feasibility of the Banda Aceh - Nagan Raya flight route. The passenger demand is obtained from independent variable and dependent variable from socio economic data which then analyzed using Ordinary Least Square (OLS) method with multiple linear regression and Software Statistical Product and Service Solution (SPSS) assistance. The modeling obtained is Y = 1194,374 – 0,068X3 where X3 is the number of domestic tourists. From the modeling results it is known that the number of passengers for the next 6 years has increased.   The result of financial feasibility analysis using discount rate 15% is obtained at sixth year (year 2021) with BCR equal to 0,348, NPV equal to Rp. (30.651.570.332), and the value of PBP obtained is 45,3 or 45 years 3 months where the value exceeds the company's payback period of 6 years. From the analysis it is known that for the Banda Aceh - Nagan Raya flight route the project benefits are less than the economically needed costs so the project is not feasible to be implemented.Abstrak: Kabupaten Nagan Raya berada pada bagian barat Provinsi Aceh. Kabupaten ini berjarak 287 km dari Kota Banda Aceh dimana moda transportasi utama adalah angkutan darat dengan waktu tempuh kurang lebih 6 jam. Jalur darat menuju Kabupaten ini melalui pegunungan yang saat musim hujan sering terjadi longsor. Sehingga diperlukan transportasi udara yang dapat membantu kelancaran mobilitas serta meningkatkan perekonomian penduduk serta dapat mengantisipasi penyaluran bantuan, evakuasi korban secara cepat ketika terjadinya bencana. PT Susi Pudjiastuti merupakan operator penerbangan perintis yang melayani penerbangan rute Banda Aceh – Nagan Raya. Penelitian ini bertujuan untuk mengetahui demand penumpang serta kelayakan finansial rute penerbangan Banda Aceh – Nagan Raya. Demand penumpang didapatkan dari variabel bebas dan variabel terikat dari data sosio ekonomi yang kemudian dianalisis menggunakan metode Ordinary Least Square (OLS) dengan regresi linier berganda dan bantuan Software Statistical Product and Service Solution (SPSS). Pemodelan yang diperoleh yaitu Y = 1194,374 – 0,068X3 dimana X3 adalah jumlah wisatawan domestik. Dari hasil pemodelan tersebut diketahui bahwa jumlah penumpang untuk 6 tahun mendatang mengalami peningkatan. Hasil analisa kelayakan finansial dengan menggunakan discount rate 15% diperoleh pada tahun ke 6 (tahun 2021) dengan nilai BCR sebesar 0,348,  NPV sebesar Rp. (30.651.570.332),-, dan nilai PBP yang diperoleh yaitu 45,3 atau 45 tahun 3 bulan dimana nilai tersebut melebihi periode pengembalian perusahaan yaitu 6 tahun. Dari analisa tersebut diketahui bahwa untuk rute penerbangan Banda Aceh – Nagan Raya manfaat yang ditimbulkan proyek lebih kecil dari biaya yang diperlukan secara ekonomi sehingga proyek tidak layak untuk dilaksanakan.